Rss-Based Information Delivery Model for Learning Management System - Bagherpour, Solmaz (2008)
In modern education, e-learning or Internet enabled learning has been extensively used by teaching and learning institutions, especially by higher education for improving their educational services. Learning Management Systems (LMS) are one of the important parts of e-learning solutions for providing learning contents and learning information during the educational process. Information delivery as main functionality of these systems has a vital role in the success of these systems in achieving their goals. An LMS with growing number of users, courses, and frequently updated learning information resources needs a systematic, fast and easy to use information delivery service which can support personalization also. As a response to this need and with considering technical and pedagogical benefits of RSS (Really Simple Syndication), this research applied a combination of RSS 2.0 and RSS 1.0 to design a new RSS-based information delivery framework for LMSs. The proposed RSS based information delivery framework is implemented on e- SPRINT, an existing LMS at Universiti Putra Malaysia as object of experiment, and evaluated regarding to the impact of RSS-based information delivery framework in users satisfaction and usability of the LMS in information delivery. Based on the analysis of the results of experimental design there is positive changes in users satisfaction with information delivery after using the framework compared to before using the framework. According to usability evaluation of the RSS information delivery framework also, positive changes of user perception from the aspect of usability in information delivery has been gained. It is mentionable that the scope of the study was limited to the case study system. The contribution of this study was the design and development of an RSS-based information delivery model for LMSs to support systematic fast and easy to use information delivery.